Novel sulfonic acid functionalized silica supported isonicotinic acid catalyst for conversion of 2-methylfuran to diesel fuel precursors - Tarade, Komal P.; Kamble, Sanjay P.; Rode, Chandrashekhar V. (Catalysis Letters, 2024)
Polyfuranic compounds produced after carbon up-gradation of 2-methylfuran by acid catalyzed C-C bond forming reactions when undergo hydro-deoxygenation produce diesel fuel. Herein, we prepared a simple and novel silica supported sulfonic acid functionalized isonicotinic acid SO3H-INA@SiO2 catalyst by treating isonicotinic acid with chlorosulphonic acid followed by heterogenization on silica. This heterogeneous solid acid catalyst was explored for the solvent free conversion of 2-methylfuran to diesel fuel precursors of C-15 and C-20 units via tandem ring opening followed by condensation sequence. Under optimized reaction conditions, SO3H-INA@SiO2 was able to convert, 2-methylfuran completely into condensation products such as 5,5-bis(5-methylfuran-2-yl)pentan-2-one (1) and 2,4,4-tris(5-methylfuran-2-yl)pentan-1-ol (2) with 19% and 67% yields, respectively. The heterogeneous SO3H-INA@SiO2 catalyst was successfully recycled up to six consecutive runs without loss of its activity. The SO3H-INA@SiO2 catalyst offered superior activity as compared to the commercially available -SO3H functionalized resins. Superior activity of the prepared catalyst could be attributed for its higher acidity, smaller particle size and high surface area. Structure of the prepared catalyst was confirmed by FTIR and solid state NMR. Total acidity of the prepared catalyst was determined by acid-base titration.
Keywords: 2-Methylfuran; Diesel fuel; heterogeneous catalyst; Ionic solid; solid acid